If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(s + 1) = -45 Reorder the terms: -10(1 + s) = -45 (1 * -10 + s * -10) = -45 (-10 + -10s) = -45 Solving -10 + -10s = -45 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -10s = -45 + 10 Combine like terms: -10 + 10 = 0 0 + -10s = -45 + 10 -10s = -45 + 10 Combine like terms: -45 + 10 = -35 -10s = -35 Divide each side by '-10'. s = 3.5 Simplifying s = 3.5
| -5=(m-1) | | 2(x-1)+2(x-2)=10 | | 6(x+1)+4=7x+1 | | f(x)=5x^4+2x | | 4(3s+20)=80 | | y=ln(1.07) | | 500x+24=60 | | -5+10y=x | | X^2+6x-90=8 | | 2log(2x)=7 | | 2=-18+4x | | Logx+2=4 | | x(x^2+16+64)=9(x+8) | | 0.25x+1.5=7.5 | | 3x^4-8=56 | | 6p^2-11=0 | | 26/30x24000 | | -6(5-2x)=q | | 4/10-x)=25-x | | 2P^2-20P+32=0 | | x^(5/4) | | 3y+7x=42 | | x^5/4 | | 10=3r+7r | | X+240y=186 | | 3a-1.2=4 | | 4x+160y=224 | | X+3(x-1)=8-4(2x+3) | | 4(10-x)=25-x | | 25k^2+40k-20=0 | | A=90(n-5) | | 2(3a-1)=2(a+1) |